2013
DOI: 10.1038/ncomms2778
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Wnt1 expression in response to ecdysteroid generates twin-spot markings on caterpillars

Abstract: Among various pigmentation patterns on caterpillars, sequential spot markings are often observed and used for aposematic colouration. In contrast to adult wings, caterpillar cuticle markings are repeatedly generated at each moult, but little is known about how the patterns are formed and maintained periodically. Here we focus on a silkworm mutant, multi lunar (L), with twin-spot markings on sequential segments. Positional cloning of L and expression analyses reveal that cis-regulatory change in Wnt1 is respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 41 publications
(43 reference statements)
2
65
0
Order By: Relevance
“…We recently found a specialized cuticular structure designated 'bulge' in the crescent marking area, in which Wnt1 was ectopically expressed and that Wnt1 expression in the larval epidermis had the potential to cause twin spot markings 32 . In this study, using in vivo electroporation, we observed that ectopically expressed Wnt1 induced apt-like expression and melanin pigmentation in þ p epidermis but not in p epidermis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently found a specialized cuticular structure designated 'bulge' in the crescent marking area, in which Wnt1 was ectopically expressed and that Wnt1 expression in the larval epidermis had the potential to cause twin spot markings 32 . In this study, using in vivo electroporation, we observed that ectopically expressed Wnt1 induced apt-like expression and melanin pigmentation in þ p epidermis but not in p epidermis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, larval markings should be repeatedly redrawn at each larval moult, which is different from adult pigmentation that occurs only once during metamorphosis. We recently showed that the moulting hormone ecdysteroid possibly regulated larval pigmentation through the function of Wnt1 in lepidopteran spot markings 32 or E75 in eye spots of the swallowtail butterfly 52 . We speculate that in contrast to adult pigmentation, module-type control of gene expression of the melanin synthesis genes is necessary for repeated pigmentation in the larval epidermis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these studies lack the phylogenetic resolution and replication observed in butterflies, they provide one of the most detailed mechanistic accounts of truly novel traits, where the deployment of Wnt expression in three different body regions is driven by independent cis-regulatory changes. Of note, wg is also associated to color patterns and wing contours in both flies and butterflies (Macdonald et al 2010;Martin and Reed 2010;Koshikawa et al 2015), and a redeployment of this gene to new body regions is likely to drive the evolution of new patterns as well, as it seemed to have occurred during the evolution of larval cuticle patterns in Lepidoptera (Yamaguchi et al 2013). We note that while Koshikawa et al did not detect any pattern-related Wnt6 and Wnt10 expression in D. guttifera developing wings ; S. Koshikawa, personal communication), these two paralogs are co-deployed with wg in butterflies where they may underlie a more complex architecture, with partially redundant ligand activities (Martin and Reed 2014).…”
Section: Ligand Gene Modularity Allows Interspecific Differencesmentioning
confidence: 99%